Recommendations for the Management of Hypertensive Disorders of Pregnancy in China: Based on the A Summary of the 2023 Society of Obstetric Medicine of Australia and New Zealand Hypertension in Pregnancy Guideline - FANG Xiang, SONG Haiqi, LIAO Xiaoyang, LIU Lidi, ZHANG Peng, JIA Yu, YANG Ziyu, YANG Rong, LIU Ruhui (Zhongguo quanke yixue)
Hypertensive disorders of pregnancy (HDP) is one of the most common complications of pregnancy and one of the leading causes of maternal mortality worldwide. In 2023, the Society of Obstetricians of Australia and New Zealand released the A Summary of the 2023 Society of Obstetric Medicine of Australia and New Zealand Hypertension in Pregnancy Guideline. This article interprets its key contents and proposes suggestions on non-drug intervention measures and refined management processes for HDP in China, in order to provide a new basis for the management of HDP in China.